The Impact of privatization on employment, firm performance and general economic situation in Zambia - KAITE, McBride Brian (KDI School, 2016)
Privatization is the transfer of productive asset ownership and control from the public to the private sector and this transfer of assets can be total, partial or functionary. The underperforming parastatals coupled with the ailing economy in the 1970s triggered the need to privatize a number of state owned enterprises. This was seen to be the panacea of keeping the economy on track as prescribed by the classical economic theories that claim that the private sector is more efficient than the public sector. In Zambia, privatization was implemented following the establishment of the Zambia Privatization Act. This saw over three quarters of the state owned enterprises falling into private hands in order to revitalize the economy. This study sought to establish the impact of privatisation on employment, firm performance, and the general economic situation in Zambia. The results of the study show that privatisation led to some relative improvements in the economy although the process was marred with irregularities and policy failures. For example, Mines on the Copperbelt Province were sold to foreign investors who managed to negotiate very cheap purchase prices and obtained a number of concessions that have deprived the government of huge sums of income through tax holidays and other concessions. Similarly, many citizens have not directly benefitted from the privatisation programme because they were victims of job losses and the government did not put in place any safety nets for such people resulting in the programme having a negative social impact both in the short and long terms. Inspite of these policy failures and considering the poor state of the economy prior to the privatisation exercise, the programme has scored some notable successes. For instance, the sale of Mines on the Copperbelt province saw a lot of positive developments taking place in terms of plant rehabilitation, new plants being opened up and so forth. Employment levels grew after privatization and production of copper and other minerals such as Cobalt increased to meaningful levels. Even with the privatization of banks such as Zanaco, success was the outcome. It, too, embarked on an expansion programme and introduced a number of facilities as such Xapit features and increased its ATMs countrywide, increased its workforce and paid huge sums in form of dividends to government. Both the mining and financial sectors had created positive levels of impact on variables such as firm performance, standard of living and employment. The mining sector alone made a contribution of 1.7% of the total labour force in 2012. In the same year, foreign direct investment as far as the mines were concerned stood at 86% with exports averaging 80% and government revenue standing at about 25%. From the foregoing, the study has revealed overall that privatisation of SOEs is good for the economy of a country but is not the end in itself. There is need to have a good policy framework in place to support the exercise. In the same vein, the study revealed that other reform programmes can produce similar if not better results compared to privatisation. Countries like Korea and Japan have employed programmes that were aimed at improving the management of SOE through restructuring and they produced far better results than what Zambia achieved through privatisation. In view of the above, the study has made some recommendations aimed at redressing the challenges and failures noted in the privatisation programme in order to avoid similar pitfalls in the future. The paper recommends that rather than privatizing the remaining SOEs in Zambia, different policies of reforms to turn around underperforming SOEs should be adopted by the Zambian government. The paper also recommends that should the government decide to privatize the remaining SOEs, programs aimed at mitigating the negative social effects of privatisation should be drawn up to serve as safety nets for those affected. For example, a law should be passed which requires that employees are given entrepreneurial training before being laid off by the company after the privatisation program. This would prepare them to survive and earn income in the private sector even if they fail to find alternative jobs.
Thesis(Master) --KDI School:Master of Public Policy,2016